Effects of Blended-Cement Paste Chemical Composition Changes on Some Strength Gains of Blended-Mortars - Mehmet Serkan Kirgiz (The Scientific World Journal)
Effects of chemical compositions changes of blended-cement pastes (BCPCCC) on some strength gains of blended cement mortars (BCMSG) were monitored in order to gain a better understanding for developments of hydration and strength of blended cements. Blended cements (BC) were prepared by blending of 5% gypsum and 6%, 20%, 21%, and 35% marble powder (MP) or 6%, 20%, 21%, and 35% brick powder (BP) for CEMI42.5N cement clinker and grinding these portions in ball mill at 30 (min). Pastes and mortars, containing the MP-BC and the BP-BC and the reference cement (RC) and tap water and standard mortar sand, were also mixed and they were cured within water until testing. Experiments included chemical compositions of pastes and compressive strengths (CS) and flexural strengths (FS) of mortars were determined at 7th-day, 28th-day, and 90th-day according to TS EN 196-2 and TS EN 196-1 present standards. Experimental results indicated that ups and downs of silica oxide (SiO2), sodium oxide (Na2O), and alkali at MP-BCPCC and continuously rising movement of silica oxide (SiO2) at BP-BCPCC positively influenced CS and FS of blended cement mortars (BCM) in comparison with reference mortars (RM) at whole cure days as MP up to 6% or BP up to 35% was blended for cement.